STUDI EKSTRAK n-HEKSANA DARI KULIT BATANG KANDIS HUTAN (Garcinia cymosa) - Darwati; Nurlelasari; Tri Mayanti; Unang Supratman (Jurnal Penelitian Hasil Hutan, 2025)
Plants of Garcinia genera (Fam: Guttiferae) that grows in Indonesia's tropical forests are potential of triterpenoid compounds contents. Garcinia cymosa has been reported as the main source of triterpenoid compounds which provided useful biological activity such as anti-inflammatory, antibacterial, antifungal, antioxidant, cytotoxic, and anti-HIV. Currently, data and information of triterpenoid compounds in the G. cymosa is relatively low. This paper studies triterpenoid compound of G. cymosa. This compound was obtained from macerated G. cymosa stem bark using n-hexane solvent. G. cymosa bark was macerated using n-hexsana solution, which was them separated and purified by chromatography method, to produce pure isolate in the form of white needle crystals (10.8 mg). The chemical structure was then determmined by using spectroscopy methods of IR, 1D-NMR, 2D-NMR, and mass spectroscopy compared with published structure. Result show friedelin compound was succesfully isolated from extracted n-heksana of G. cymosa bark.